The subgingival periodontal microbiota of the aging mouth - Feres, Magda; Teles, Flavia; Teles, Ricardo; Figueiredo, Luciene Cristina; Faveri, Marcelo (Periodontology 2000, 2016)
Different mechanisms have been hypothesized to explain the increase in prevalence and severity of periodontitis in older adults, including shifts in the periodontal microbiota. However, the actual impact of aging on the composition of subgingival biofilms remains unclear. In the present article, we provide an overview of the composition of the subgingival biofilm in older adults and the potential effects of age on the oral microbiome. In particular, this review covers the following topics: (i) the oral microbiota of an aging mouth; (ii) the effects of age and time on the human oral microbiome; (iii) the potential impact of inflammaging and immunosenescence in the host–oral microbiota interactions; and (iv) the relationship of the aging oral microbiota and Alzheimer's disease. Finally, we present analyses of data compiled from large clinical studies that evaluated the subgingival microbiota of periodontally healthy subjects and patients with periodontitis from a wide age spectrum (20–83 years of age).